2021
DOI: 10.3390/ijms22158298
|View full text |Cite
|
Sign up to set email alerts
|

PPARs as Metabolic Sensors and Therapeutic Targets in Liver Diseases

Abstract: Carbohydrates and lipids are two components of the diet that provide the necessary energy to carry out various physiological processes to help maintain homeostasis in the body. However, when the metabolism of both biomolecules is altered, development of various liver diseases takes place; such as metabolic-associated fatty liver diseases (MAFLD), hepatitis B and C virus infections, alcoholic liver disease (ALD), and in more severe cases, hepatocelular carcinoma (HCC). On the other hand, PPARs are a family of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 153 publications
0
20
0
Order By: Relevance
“…Lipid-derived metabolites serve as the natural ligands of PPARs. The tissue distribution of PPAR subtypes and their endogenous ligands and target genes are summarized in a review by Monroy-Ramirez, et al ( Monroy-Ramirez et al, 2021 ). PPARα is a regulator of fatty acid metabolism and involved in substrate transport, substrate oxidation, and oxidative phosphorylation (OXPHOS); PPARδ plays a vital role in fatty acid oxidation and blood glucose regulation; PPARγ can facilitate energy storage by promoting adipogenesis and lipid synthesis in different cell and play a major role in adipocyte differentiation ( Christofides et al, 2021 ).…”
Section: Ppar Signalingmentioning
confidence: 99%
“…Lipid-derived metabolites serve as the natural ligands of PPARs. The tissue distribution of PPAR subtypes and their endogenous ligands and target genes are summarized in a review by Monroy-Ramirez, et al ( Monroy-Ramirez et al, 2021 ). PPARα is a regulator of fatty acid metabolism and involved in substrate transport, substrate oxidation, and oxidative phosphorylation (OXPHOS); PPARδ plays a vital role in fatty acid oxidation and blood glucose regulation; PPARγ can facilitate energy storage by promoting adipogenesis and lipid synthesis in different cell and play a major role in adipocyte differentiation ( Christofides et al, 2021 ).…”
Section: Ppar Signalingmentioning
confidence: 99%
“…Different isoforms of PPARs (PPARα, PPARβ/δ, and PPARγ) have different tissue distribution, affinity, and specificity for agonists. All isoforms participate in lipid homeostasis and glucose regulation [88] . Fibroblast growth factors (FGFs) are a large family involved in a myriad of biological functions, among which FGF19 and FGF21 participate in inter-organ endocrine signaling axes including bile acid, glucose, and lipid metabolism.…”
Section: Modulators Of Metabolism Disordersmentioning
confidence: 99%
“…All isoforms participate in lipid homeostasis and glucose regulation. [88] Fibroblast growth factors (FGFs) are a large family involved in a myriad of biological functions, among which FGF19 and FGF21 participate in inter-organ endocrine signaling axes including bile acid, glucose, and lipid metabolism. Endocrine FGFs may serve as risk factors, biomarkers, or even treatment targets for MAFLD.…”
Section: Modulators Of Metabolism Disordersmentioning
confidence: 99%
“…PPARs are a family of ligand-dependent transcription factors composed of three subtypes PPARα, PPARβ/δ, and PPARγ with different functions, distributions, affinities, and specificities for their ligands. Each of them has distinct pleiotropic roles in the modulation of energy, lipid, cholesterol, and bile acid homeostasis ( Ghonem et al, 2015 ; Tanaka et al, 2017 ; Monroy–Ramirez et al, 2021 ). In this regard, it has been demonstrated that PPARα activation is capable of modulating bile acid metabolism due to activation of genes involved in bile acid synthesis and transportation.…”
Section: Introductionmentioning
confidence: 99%